Motivation to Community for Following Aerobic Sports - Kusmiyanti, Dhian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this study is to determine the role of motivation what is the basis of the community following aerobic gymnastics. The method used in this research is using qualitative descriptive. Data collection techniques used are using survey techniques. The research results show that the role of motivation for the public to participate in aerobic exercise is very important. People who follow this aerobic gymnastics come from different backgrounds that is from the educational environment both teachers and students, teenagers, housewives, and elderly. The results of five aerobic gymnastics workshops namely Yoyok Fans Community amounted to 18 people, Maria Center amounted to 63 people, Lotte Mart Morning Gymnastic Community, 82 people, Ira Gymnastic Studio numbered 12 people and Dee Dee Gymnastic Studio numbered 11 people. Of the five gymnastics studios studied then the total amounted to 186 people. The motivation of society is so that body become healthy and fit 108 people then get 58,06%, recreation 30 people then get 16,13%, add friend 21 people then get 11,29%, want to channel knowledge to other people equal to 14 people then obtained 7.53%, and became the champion when following the race 13 people then obtained 6.98%